Physical activity promotion in care homes. Issue 4 (11th December 2017) - Turpie, Lindsay; Whitelaw, Sandy; Topping, Christopher
Abstract : Purpose: The purpose of this paper is to report on the implementation of a physical activity (PA) scheme – Let's Motivate (LM) – within private care homes (CHs) in Dumfries and Galloway (D&G), Scotland; aiming to provide an insight into the different factors which might contribute to its success and further sustainability. Design/methodology/approach: A qualitative study is described in which one-to-one semi-structured interviews were carried out with eight key staff involved in implementing the project within two purposively sampled CHs; in order to explore their views and experiences of implementation. Findings: The paper provides an insight into the different factors which stand to both promote and impede the successful implementation of LM, within the two CHs involved. Originality/value: This paper explores a new and innovative PA initiative in CHs in D&G, Scotland. Studies exploring the factors which can both promote and impede implementation are important as they can help to usefully inform the implementation and sustainability of initiatives.